A Blinded Study Using Celecoxib for Prevention of Morphine Induced Pruritus in Patients Undergoing Cesarean Section - Saghar Samimi; Fatemeh Davari Tanha; Masume Malekian (Tehran University of Medical Sciences, 2011)
Objective: we aimed to evaluate the efficacy of celecoxib in reducing Intrathecal morphine-induced pruritus in parturient undergoing cesarean section delivery under spinal anesthesia. Materials and methods: In a randomized double-blind placebo controlled study 126 women undergoing elective cesarean section under spinal anesthesia (0.5% bupivacaine 12mg plus 0.2 mg preservativefree morphine )were randomly allocated to receive celecoxib 400 mg or placebo, 2 hours prior to surgery. Severity of pruritus and pain score and frequency of opioid's side effects were recorded. Results: patients receiving celecoxib had significantly lower pruritus incidence and severity at 30 min,2,4 and 8 hours (40% versus 82%), but not at 12 and 24 hours postoperatively. Also there was a reduction in pain score but it was not significant (1.5±0.5 versus 1.9±0.65).Analgesic requirement was similar between two groups. Conclusion: Oral administration of celecoxib significantly reduced Intrathecal morphine-induced pruritus in parturient undergoing cesarean section under spinal anesthesia. There was no significant difference in pain scores and analgesic requirement.